The scripture on great peace: the Taiping jing and the beginnings of Daoism - Hendrischke, Barbara (Daoist classics series, 2006)
This first Western-language translation of one of the great books of the Daoist religious tradition, the Taiping jing, or ''Scripture on Great Peace, '' documents early Chinese medieval thought and lays the groundwork for a more complete understanding of Daoism's origins. Barbara Hendrischke, a leading expert on the Taiping jing in the West, has spent twenty-five years on this magisterial translation, which includes notes that contextualize the scripture's political and religious significance. Virtually unknown to scholars until the 1970s, the Taiping jing raises the hope for salvation in a pra